Civil liability arising from environmental pollution damage in the digital transformation: A national and international legislative perspective - YOUCEF, AHMOUDA; Rachid, FEREDJ; YAMINA, HAMDI PACHA; LAID, SAHRAOUI (Journal of Ecohumanism, 2025)
The digital transformation has createdunprecedentedlegal challenges in the area of civil liability for environmental pollution damage, as reliance on digital systems and predictiveartificial intelligence technologies has become a keyelement in managingpollutingactivities and monitoring environmentalrisks. However, this new reality raisesdelicate issues concerning the determination of the basis of liability, the attribution of fault, the proof of causality, and the formulation of mechanisms for assessing compensation for environmental damage in a complex digital environment.This paperaims to analyse the extent to whichtraditionalrules of civil liabilitycanaccommodatethese changes, whileproposingadvancedlegislativemechanismsthatensure effective protection of the environmentwithouthindering digital innovation.